Interstitial Score and Concentrations of IL-4Rα, PAR-2, and MMP-7 in Bronchoalveolar Lavage Fluid Could Be Useful Markers for Distinguishing Idiopathic Interstitial Pneumonias - Bruzova, Magdalena; Pavlova, Martina; Matej, Radoslav; Sterclova, Martina; Vasakova, Martina (Diagnostics (Basel, Switzerland), 2021)
Idiopathic interstitial pneumonia (IIP) entails a variable group of lung diseases of unknown etiology. Idiopathic pulmonary fibrosis, nonspecific interstitial pneumonia, interstitial lung diseases related to connective tissue disease (CTD-ILD), and hypersensitivity pneumonitis (HP) can manifest with similar clinical, radiological, and histopathological features. In a differential diagnosis, biomarkers can play a significant role. We assume that levels of specific cyto- or chemokines or their receptors can signal pathogenetic processes in the lungs. Eighty patients with different types of idiopathic interstitial pneumonia were enrolled in this study. Cell counts and concentrations of tumor necrosis factor (TNF)-α, interleukin-4 receptor α, proteinase-activated receptor (PAR)-2, matrix metalloproteinase (MMP)-7, and B cell-activating factor were measured in bronchoalveolar lavage fluid using commercial ELISA kits. High resolution computer tomography results were evaluated using alveolar and interstitial (IS) score scales. Levels of TNF-α were significantly higher in HP compared to fibrosing IIP (p < 0.0001) and CTD-ILD (p = 0.0381). Concentrations of IL-4Rα, PAR-2, and MMP-7 were positively correlated with IS (p = 0.0009; p = 0.0256; p = 0.0015, respectively). Since TNF-α plays a major role in inflammation, our results suggest that HP is predominantly an inflammatory disease. From the positive correlation with IS we believe that IL-4Rα, PAR-2, and MMP-7 could serve as fibroproliferative biomarkers in differential diagnosis of IIP.
Keywords: idiopathic interstitial pneumonias; interstitial score; bronchoalveolar lavage fluid; matrix metalloproteinase-7; tumor necrosis factor-α; B cell-activating factor; proteinase-activated receptor-2; interleukin-4 receptor α